2022
DOI: 10.21273/hortsci16690-22
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated Water Temperature on Growth of Basil Using Nutrient Film Technique

Abstract: Hydroponic systems have become increasingly popular for growers in recent years for year-round local production. Whereas optimal air temperature for plant growth has been considered, optimal root zone temperatures have not been examined as thoroughly. The objective of this research was to determine the optimal water temperature for growing different types of basil hydroponically. Research was conducted at the greenhouses in Stillwater, OK. Seventeen cultivars were selected from six main types of basil and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Some studies confirmed that root zone temperature regulation positively affected crop growth [17][18][19], and the irrigation water temperature was one of the main factors affecting root zone temperature. Several researchers mainly studied the influence of warm-water irrigation on flowers and field crops [20,21], and confirmed the significance of warm-water irrigation for crop growth. For vegetable facilities, warm-water irrigation research was mainly conducted on leaf vegetable crops [22].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies confirmed that root zone temperature regulation positively affected crop growth [17][18][19], and the irrigation water temperature was one of the main factors affecting root zone temperature. Several researchers mainly studied the influence of warm-water irrigation on flowers and field crops [20,21], and confirmed the significance of warm-water irrigation for crop growth. For vegetable facilities, warm-water irrigation research was mainly conducted on leaf vegetable crops [22].…”
Section: Introductionmentioning
confidence: 99%
“…Instant monitoring of the element ratios in the nutrient solution is crucial for both system control and preventing chemical nutrient waste during production. Upon reviewing the relevant literature, it is observed that methods such as measuring electrical conductivity (EC), pH measurement, and ion chromatography results are used to obtain information about the chemical components in the nutrient solution in hydroponic farming [9][10][11][12][13] . While methods such as measuring electrical conductivity and pH levels of the solution provide quick measurement results, they cannot provide precise results about the nutrient elements in the solution.…”
Section: Introductionmentioning
confidence: 99%